Why geometry feels difficult: A phenomenological inquiry into junior high school students’ learning experiences in Indonesia - Raodatul Ainiyah; Muh Rusmayadi; Samsul Bahri (Panicgogy International Journal, 2025)
Geometry is an essential component of mathematics that supports students in developing logical, critical, and spatial thinking skills, yet many students continue to find this material difficult to master. This study explored, in depth, eighth-grade students’ experiences of learning geometry through a hermeneutic phenomenological approach. Data were collected using an open-ended questionnaire completed by ten eighth-grade students (5 males and 5 females, aged 13-15) from a private junior high school in Mataram City, West Nusa Tenggara, Indonesia, and were analyzed following Braun and Clarke’s thematic analysis, assisted by an artificial intelligence tool (ChatGPT) during initial coding and subsequently verified manually by the researchers. The analysis produced six initial codes, condensed into five categories and, ultimately, three overarching themes: (1) pedagogical barriers and limited use of learning aids, (2) the complexity of geometry concepts, and (3) the lack of contextual application and student confidence. These findings indicate that geometry learning difficulties are not caused solely by students’ cognitive limitations but are closely related to instructional strategies, the nature of the material itself, and students’ psychological readiness. By foregrounding students’ own voices, this study offers a more holistic account of geometry learning difficulties than achievement-score data alone can provide. It recommends implementing more contextual, adaptive, and supportive learning strategies, using visual media aligned with students’ Van Hiele levels of thinking, to strengthen their spatial reasoning skills and confidence.